Two Genes Homologous with Human Protein S cDNA Are Located on Chromosome 3 - Amstel, J K Ploos van; van der Zander, A L; Bakker, E; Reitsma, P H; Bertina, R M (Thrombosis and Haemostasis, 1987)
A cDNA coding for the carboxy-terminal region of human protein S and containing a complete 3’-untranslated region, was isolated by a combination of antibody screening of a λgt11 human liver cDNA expression library and in situ hybridization of a pUC9 human liver cDNA library.Hybridization analysis of human total DNA with radiolabelled non-overlapping cDNA restriction fragments revealed the existence of two genes per haploid genome homologous with the protein S cDNA. Both genes were mapped to chromosome 3 using human-rodent cell hybrids. Neither of the genes showed polymorphism for sixteen different enzymes upon hybridization with the protein S cDNA.
Keywords: Protein S; Gene; Chromosome; RFLP; Thrombosis